OPTIMIZATIONOF ANDROID MEDIA TO ENHANCE THE ABILITY TO READ THE WIRING DIAGRAM OF THE CONVENTIONAL IGNITION SYSTEM - Al Majasan Sah, Fahmi Raqib; Darmawan, Bambang; Sriyono, Sriyono; Wiyono, Apri (Universitas Pendidikan Indonesia, 2020)
The implementation of this research was motivatedby the low results of student examinations in the Automotive Engine Electricity subject in 2017-2018, namely there were 27 students with an assessment standard of 7.5 after taking the average score of students at a value of 5.17 which indicates the average value of students. is far below the minimum completeness criteria value.Researchersestimatethatthelowachievementofstudenttestscoresisduetolowunderstandingof learning materials, and understanding of this material is influenced by the application of learning mediathatisnotoptimal.Learningmediaisessentiallyabridgeoflearningmessagesconveyedby lecturers to students so that they can be absorbed quickly and precisely according to their purpose. Some of the optimal application of learning media can use Android-based media, especially Unity Media.Researchersstigmatize thattheuseofAndroid-basedlearningmediawithUnitymediacan improve student learning outcomes. The implementation of this study aims to determine whether the use of android-based applications can significantly improve students' ability to read conventional ignition wiring diagrams in the Automotive Engineering course. Retrieval of data in thisstudywastaken fromasampleofautomotiveconcentrationmechanicalengineeringeducation students who are currently taking Automotive Engine Electrical courses. The research design that the researchers used was the Experiment type One Group Pre-test-Post test Design. Based on the research data, the data shows that there is a significant increase in student achievement, which is obtainedbasedonthepretestandposttestscores.TheaverageN-gainscoreobtainedfromthisstudy is 0.41 in the mediumcategory.